2000
DOI: 10.1002/hep.510310127
|View full text |Cite
|
Sign up to set email alerts
|

Gastric mucosa as an additional extrahepatic localization of hepatitis C virus: Viral detection in gastric low-grade lymphoma associated with autoimmune disease and in chronic gastritis

Abstract: Hepatitis C virus (HCV) has been localized in several tissues besides the liver. 1 The definition of the possible extrahepatic localizations of the virus may be relevant to better address the issue of some of the extrahepatic manifestations of chronic HCV infection. As regards the gastric microenvironment, gastric lymphoma has been reported in patients with HCV infection, 2-6 and a relationship was noticed between HCV infection and B-cell clonal expansion in chronic gastritis lesions in Sjö gren' s syndrome (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 35 publications
(75 reference statements)
0
44
0
1
Order By: Relevance
“…Current knowledge derived from epidemiological data [22][23][24][25][26][27][28][29][30], regression of HCV-LPD after HCV eradication [30], in situ studies of the presence of HCV (RNA and structural proteins) in stromal cells surrounded by the lymphoproliferative processes [11,26,31] and structural homology of the antigen-binding sites of the IgR expressed by HCV-NHL with antibodies specific for the E2 protein of HCV [12,24] strongly suggest that a protein of HCV, alone or in association with the Fc part of the immunoglobulin [32,33], may express the antigenic epitope(s) involved in HCV-LPD.…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge derived from epidemiological data [22][23][24][25][26][27][28][29][30], regression of HCV-LPD after HCV eradication [30], in situ studies of the presence of HCV (RNA and structural proteins) in stromal cells surrounded by the lymphoproliferative processes [11,26,31] and structural homology of the antigen-binding sites of the IgR expressed by HCV-NHL with antibodies specific for the E2 protein of HCV [12,24] strongly suggest that a protein of HCV, alone or in association with the Fc part of the immunoglobulin [32,33], may express the antigenic epitope(s) involved in HCV-LPD.…”
Section: Discussionmentioning
confidence: 99%
“…Whether a putative anti-HCV (cross-)reactivity may be implicated in selected cases (ref. 40 and see patient 3 in group 1) also warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR, in situ hybridization, and immunochemistry studies have demonstrated that HCV colocalizes with low grade B-cell NHL tissue. In contrast, HCV-positive cells were primarily located along the edges of low grade B-cell NHL tissue and were only rarely observed to be interspersed within it (23)(24)(25). Additionally, neoplastic tissue biopsies from two HCV-positive patients with high grade B-cell NHL were found to be HCV-negative (26).…”
Section: Genesis Of B-cell Hcv-associated Lymphomasmentioning
confidence: 99%